Internalisasi Nilai-Nilai Aswaja Dalam Pendidikan Islam Sebagai Upaya Deradikalisasi di Poncokusumo Malang - Rif’an Kholili; Mohammad Afifulloh; Muhammad Sulistiono (VICRATINA, 2019)
So far, radical Islamic groups are known not to respect and be very anti against the culture and traditional values of Indonesian Muslims. Many religious traditions are carried out by Indonesian people, which according to them are bid'ah acts because they never existed at the time of the Prophet and were never taught by the Prophet. It is not surprising that they are very keen to attack religious rituals and rituals that have taken root in most of the Indonesian Muslim community, one of which happened to the condition of the people in Poncokusumo Malang who have begun to have several doctrinal movements to dislike the traditions or culture in their surroundings tend to be antipathic towards the surroundings. Based on this context, the main problem of this research is how to internalize the values of Islamic education in the NU Poncokusumo Malang environment and based on these main problems, the formulation of the problem of this research is the condition of the radicalization of religious understanding in Poncokusumo, then what in internalizing Aswaja Values in the Poncokusumo Environment is done as an effort in the process of Deradicalization in the Poncokusumo Malang Environment in this study researchers used a qualitative approach to describe the variable as it is.